A German Model Project for Workplace Health Promotion— Flow of Communication, Information, and Reasons for Non-Participation in the Offered Measures - Lutz, Regina; Fischmann, Wolfgang; Drexler, Hans; Nöhammer, Elisabeth (International Journal of Environmental Research and Public Health, 2022)
Background: Workplace health promotion (WHP) as a part of workplace health management (WHM) was strengthened in German legislature with the Prevention Act of 2015. However, smaller enterprises often do not offer WHM or WHP. Accordingly, a model-project for improving the uptake and implementation, particularly in micro-, small, and medium-sized enterprises (MSMEs) was carried out. The aim of the study was to determine reasons for non-participation in WHP offers and analyze communication issues, both from the employee’s and employer’s perspective. Methods: In total, 21 managers or persons responsible for WHP participated in the first online survey between March and April 2020, and 156 employees responded to the second online survey between June and October 2021. The importance of barriers and communication issues was investigated. Based on a principal component analysis on non-participation, differences regarding sociodemographic variables were analyzed. Results: Most employees knew about the offered measures and that the measures were cost free. There was no significant association between having communicated the offers to the employees and considering them suitable for their needs. Most of the managers or persons responsible for WHP rated the measures as sufficiently varied and allowed staff to take part during working-time. Reasons for non-participation from the managers’ point of view were travel time to the location of the offers, lack of time, and a missing fit between offers and employees’ needs. From the employees’ point of view, workload (including working time) was the main barrier to participation. Conclusions: For the practical implementation of model projects in MSMEs, special attention should be paid to ensuring opportunity to participate, which may be easier with in-house offers.
CRIS-Team Scopus Importer:2022-07-08
Keywords: communication; dissemination; Germany; health promotion; information; medium-sized businesses; microenterprises; occupational health; small businesses